COMPOSITION OF CAPCHESOF KELONG BILIS FISHING GEAR BEFORE AND AFTER MIDNIGHT IN THE VILLAGE MALANG RAPAT OF SUB DISTRICT BINTAN GUNUNG KIJANG PROVINCE ISLANDS RIAU - Amiruddin Rambe; Arthur Brown; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in September 2015 in the village of Malang RapatMountain Kijang Bintan regency Islands Province Riau. The purpose of this studywas to determine the composition of catches Kelong bilis which operated at the timebefore and after midnight the day. This research was use the submisible lamp inblue colour of light. Result of this experiment showed the catches after midnightis bigger than before midnight.Keywords: Underwater Lamp (LACUBA),kelong